Golay Coded Sequences in Synthetic Aperture Imaging Systems - TROTS, Ihor; TASINKEVYCH, Yuriy; NOWICKI, Andrzej; LEWANDOWSKI, Marcin (Archives of Acoustics, 2011)
The paper presents the theoretical and experimental study of synthetic trans-mit aperture (STA) method combined with Golay coded transmission for medicalultrasound imaging applications. The transmission of long waveforms characterizedby a particular autocorrelation function allows to increase the total energy of thetransmitted signal without increasing the peak pressure. It can also improve signal-to-noise ratio and increase the visualization depth maintaining the ultrasound imageresolution.In the work the 128-element linear transducer array with 0.3 mm pitch excited bythe 8 and 16-bits Golay coded sequences as well as a one cycle at nominal frequencies4 MHz were used. The comparison of 2D ultrasound images of the tissue mimickingphantoms is presented to demonstrate the benefits of coded transmission. The imagereconstruction was performed using synthetic STA algorithm with transmit andreceive signals correction based on a single element directivity function.